Epidemiological study of cryptosporidiosis in immunocompetent & immunocompromised children, prepared parasitic antigen and used it in IFAT: Kawan.M.H ,Shether.M.M - H., Kawan M. (The Iraqi Journal of Veterinary Medicine, 2006)
An epidemiological study was done on 2 groups of children infectedwith watery diarrhea in some hospitals of Baghdad (group 1: immunocompetentoutpatients, group 2: immunosuppressed inpatients).Modified cold Ziehl Neelsen stain was used in diagnosis. The wholeoocysts antigen prepared after conduction of experimental infection in 2 calvesby using isolated oocysts from children stool, and this prepared antigen wasused in Indirect Fluorescent Antibody Technique (IFAT).The percentage of infection in the 2 groups of outpatients and inpatientswere 21.2% and 32% respectively, and there was a difference in percentage ofinfection between the 3 groups of children, the highest was 36.4% in group withleukemia and received chemical and radiotherapy.There was no significant difference between the two sexes.The clinical signs of experimental infection began after 4 days and continued for10 days. The oocysts appeared in IFAT as spherical in shape with clear wallsand bright yellowish green color. There was no significant difference betweenthe 2 methods used for diagnosis (stain and immunological test).